PENGARUH STRUKTUR MODAL, LIKUIDITAS, ARUS KAS BEBAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Widi J H, Erwin; Widyastuti, Tri; Bahri, Syamsul (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2021)
This study is to find the effect of capital structure, liquidity, free cash flow and company size to firm value with profitability as an intervening variable. Sample 10 coal companies and listed on Indonesia Stock Exchange 2014 -2018. The method of data analysis used in this research with multiple regression approach with the help of Eviews9. The result of research indicates that capital structure, liquidity, and company size have no positive and significant influence to profitability. Only free cash flow has a positive and significant influence. Capital structure, liquidity, free cash flow and company size have no positive and significant influence to value firm. Only profitability has a positive and significant influence.